Pengaruh Kemandirian Belajar, Kecemasan Matematika dan Prokrastinasi terhadap Prestasi Belajar Matematika Siswa SMP - Alimuddin; Awi Dassa; Asri Ainun Amaliah (Issues in Mathematics Education (IMED), 2022)
This research is a quantitative study with an ex post facto approach aimed to determine the effect of learning independence, mathematics anxiety, and procrastination on mathematics learning achievement of SMP. The sample in this study was 98 students of class VIII SMP. The data collection techniqueused in this research is questionnaire and test. The instruments used are questionnaire learning independence, questionnaire mathematics anxiety, questionnaire procrastination, and test mathematics learning achievement. The data analysis used the multiple linear regression analysis. The result of the research shows that: (1) learning independence, mathematics anxiety, and procrastination jointly influence student's mathematics learning achievement, (2) learning independence had a positive effect on student’s mathematics learning achievement, (3) mathematics anxiety had a negative effect on mathematics learning achievement. Student’s, (4) procrastination has a negative effect on student’s mathematics learning achievement.